Influência da abordagem tdd na qualidade de código-fonte - Farah, Julio César Marques (2013)
There are several features, in the literature, that guide the process of building software focused at creating high quality software products. Among these features is TDD - Test-Driven Development. This study evaluates the impact of the technique at the source code by comparing software metrics proposed by the software quality standards applied in two systems, developed according to the same requirements. One of these systems was built applying the mentioned technique. The results of this comparison are presented and discussed, bringing a practical view of the impact that the technique can bring to the software product, especially on aspects related to the source code.